Synthesis and Properties of a Cyclohexa‐2, 7‐anthrylene Ethynylene Derivative. (3rd November 2020) - Matsuki, Hironori; Okubo, Keisuke; Takaki, Yuta; Niihori, Yoshiki; Mitsui, Masaaki; Kayahara, Eiichi; Yamago, Shigeru; Kobayashi, Kenji
Abstract: The synthesis of a cyclohexa‐2, 7‐(4, 5‐diaryl)anthrylene ethynylene (1 ) was achieved for the first time by using 1, 8‐diaryl‐3, 6‐diborylanthracene and 1, 8‐diaryl‐3, 6‐diiodoanthracene as key synthetic intermediates. Macrocycle 1 possesses a planar conformation of approximately D 6 h symmetry, because of the triple‐bond linker between the anthracene units at the 2, 7‐positions. It was confirmed that macrocycle 1, bearing bulky substituents at the outer peripheral positions, behaves as a monomeric form in solution without π‐stacking self‐association. Macrocycle 1 has an inner‐cavity size that allows specific inclusion of [9]cycloparaphenylene ([9]CPP), but not [8]CPP or [10]CPP, through an aromatic edge‐to‐face CH‐π interaction. Abstract : The synthesis of a cyclohexa‐2, 7‐anthrylene ethynylene derivative was achieved for the first time. This macrocycle possesses a planar conformation and an inner cavity that includes [9]cycloparaphenylene through an aromatic edge‐to‐face CH‐π interaction.